Anti-oxidation uranium nitride-based composite fuel pellet and preparation method thereof

By introducing silicon carbide (SIC) in the UN fuel core block to make it diffuse distributed or three -dimensional continuous distribution, the problem of insufficient antioxidant resistance of UN fuel core blocks has significantly improved its antioxidant performance. The dynamic oxidation temperature increases by 50 by 50 Over ℃.

CN119361190APending Publication Date: 2025-01-24MATERIAL INST OF CHINA ACADEMY OF ENG PHYSICS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411502179.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing UN fuel pellets have poor structural integrity and insufficient oxidation resistance after corrosion in 360℃ water and steam for 4 hours, which limits their widespread use in commercial light water reactors.

Method used

Through the introduction of silicon carbide (SIC) in the UN fuel core block, it makes it a diffuse distribution or three-dimensional continuous distribution in the UN matrix to stimulate the crystal-crystal collaborative enhancement mechanism and improve the antioxidant performance.

Benefits of technology

The antioxidant performance of the UN fuel core block is significantly improved. The dynamic oxidation temperature is increased by more than 50 ° C than pure UN, and only a small amount of SIC adds (<10Vol %), which improves the antioxidant performance of UN.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361190A_ABST
    Figure CN119361190A_ABST
Patent Text Reader

Abstract

According to the anti-oxidation UN-based composite fuel pellet and the preparation method thereof, silicon carbide (SiC) serves as an anti-oxidation performance reinforcing phase of the UN fuel pellet, SiC is distributed in a dispersed mode or continuously distributed in a UN fuel matrix in a three-dimensional mode, and by means of the intragranular-grain boundary synergistic reinforcing effect of SiC, the anti-oxidation UN-based composite fuel pellet can be used for preparing the anti-oxidation UN-based composite fuel pellet, and the anti-oxidation UN-based composite fuel pellet can be used for improving the anti-oxidation performance of the UN fuel pellet. And the oxidation resistance of the UN fuel pellet is remarkably improved. Intragranular modification generated by solid solution reaction of trace SiC and UN can effectively enhance intrinsic oxidation resistance of a UN matrix, and meanwhile, excellent chemical inertness of a second phase of SiC can effectively inhibit grain boundary oxidation. By optimizing the morphology and distribution mode of the SiC second phase in the composite fuel pellet, the oxidation resistance of the composite fuel pellet can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nuclear fuel, and in particular to an oxidation-resistant uranium nitride-based composite fuel pellet and a preparation method thereof. Background Art

[0002] Nuclear fuel plays a core role in nuclear energy applications, and its performance is the key to the success of nuclear energy application technology and the safety of nuclear reactors. The uranium dioxide pellet-zirconium alloy cladding (UO2-Zr) fuel system widely used in commercial light water reactors currently has a huge safety hazard of too low thermal conductivity. In this context, the development of new accident tolerant fuel (ATF) has become the most concerned issue in the field of nuclear fuel. Its purpose is to improve the thermal conductivity without reducing the density of the pellets as much as possible, thereby improving the existing fuel system in terms of economy and safety.

[0003] Among various non-oxide ATFs, uranium nitride (UN) has the advantages of high melting point, high uranium density, high thermal conductivity, low specific heat, and good irradiation stability, and has received widespread attention at home and abroad in recent years. However, the bottleneck problem that limits the widespread application of UN fuel in commercial light water reactors is its poor oxidation resistance. The basic requirement for the oxidation resistance of nuclear fuel is that the pellets still maintain good structural integrity after being corroded in water and steam at 360°C for 4 hours, while UN fuel breaks and fails at less than 300°C under this condition. How to improve the oxidation resistance of UN is one of the main difficulties faced in the field of nuclear fuel.

[0004] Depositing a coating on the surface of UN fuel pellets is the most direct and effective solution to improve their corrosion resistance, but the irradiation swelling caused by long-term service of the pellets can easily lead to cracking and failure of the surface coating. Therefore, the mainstream route internationally is to prepare UN-based composite fuel pellets and directly modify UN by introducing additive phases. Among them, the most commonly used is the dispersed additive phase, which is to evenly disperse the second phase with excellent antioxidant properties on the UN grain boundary, directly hinder the diffusion of water and oxygen at the grain boundary or expect to form a passivation film on the surface of the pellet, such as UO2, UB2, U3Si2, AlN, GaN, CrN, Cr, etc. In order to ensure that the composite pellet still has a sufficiently high uranium loading after adding the second phase, the allowable second phase addition amount is not more than 20 vol%. However, such a low content of added phase cannot completely isolate the UN grains from the contact with the corrosive medium. On the other hand, most of the existing added phases will either undergo serious chemical reactions with UN and fail to exert their own antioxidant effect; or have poor physical compatibility with UN, which will accelerate the oxidation cracking of the UN pellet. As a result, even if the chemical properties of the added phase itself are very stable, it cannot improve the antioxidant ability of UN after being introduced as a second phase. Therefore, there is an urgent need to develop new UN composite fuel pellets. Summary of the invention

[0005] The present invention aims to provide a uranium nitride-based composite fuel pellet with significantly improved oxidation resistance compared with pure UN fuel pellets and a preparation method thereof.

[0006] In order to achieve the above technical objectives, the technical solution provided by the present invention is:

[0007] An oxidation-resistant uranium nitride-based composite fuel pellet comprises a uranium nitride matrix and silicon carbide, wherein the volume fraction of the uranium nitride is 90vol%-99.5vol%, the volume fraction of the silicon carbide is 0.5vol%-10vol%, and the silicon carbide is dispersedly distributed or three-dimensionally continuously distributed in the uranium nitride matrix.

[0008] The present invention provides a method for preparing an oxidation-resistant uranium nitride composite fuel pellet with SiC dispersed distribution, comprising the following steps:

[0009] Step 1: Mixing uranium nitride powder and nano silicon carbide powder to obtain mixed raw material powder;

[0010] Step 2: Sintering the mixed raw material powder obtained in step 1, and obtaining, after cooling, oxidation-resistant uranium nitride composite fuel pellets with SiC dispersed therein.

[0011] Furthermore, in step 1, the nano silicon carbide powder is SiC particles and / or SiC whiskers, the particle size of the SiC particles is 0.06-50 μm, the diameter of the SiC whiskers is 0.1-2 μm, and the length is 10-300 μm.

[0012] Furthermore, in step 1, the particle size of the UN powder is 0.3-50 μm. 235 The enrichment of U is 0.3%-19%.

[0013] The present invention also provides a method for preparing an oxidation-resistant uranium nitride composite fuel pellet having SiC in a three-dimensional continuous distribution, comprising the following steps:

[0014] Step 1: Prepare UN low-density blank from UN powder;

[0015] Step 2: crushing, screening, grinding and spheroidizing the UN low-density blank to obtain spherical UN;

[0016] Step 3: Mix the spherical UN with nano-SiC particles, so that the nano-SiC particles are evenly coated on the surface of the spherical UN to obtain SiC-UN composite powder with a core-shell structure;

[0017] Step 4: Sintering and cooling the SiC-UN composite powder to obtain an oxidation-resistant uranium nitride composite fuel pellet with three-dimensional continuous SiC distribution.

[0018] Furthermore, in step 1, the particle size of the UN powder is 0.3-50 μm. 235The enrichment of U is 0.3%-19%.

[0019] Furthermore, in step 1, the density of the UN low-density blank is 7-12 g / cm 3 .

[0020] Furthermore, in step 1, the specific method for preparing the UN low-density blank includes low-temperature pre-sintering or room-temperature dry pressing.

[0021] Furthermore, the low-temperature pre-sintering method is any one of pressureless sintering, gas pressure sintering, hot pressing sintering, hot isostatic pressing sintering, and spark plasma sintering.

[0022] The present invention has the following beneficial effects:

[0023] 1. The present invention introduces an additive phase of SiC with excellent antioxidant properties and capable of undergoing a trace modification reaction with UN into UN fuel pellets, thereby stimulating an intragranular-grain boundary synergistic enhancement mechanism and significantly improving the antioxidant properties of UN fuel pellets. Specifically, the intragranular modification effect produced by the solid solution reaction of trace SiC with UN can effectively enhance the intrinsic antioxidant properties of the UN matrix, while the excellent chemical inertness of the SiC second phase itself can effectively inhibit grain boundary oxidation.

[0024] 2. For the existing UN-based composite fuel system, even if the added phase itself is antioxidant, it is often unable to effectively enhance the antioxidant performance of the UN fuel pellets, or a large amount of addition (≥10 vol%) is required to slightly improve its antioxidant performance. In contrast, the advantage of the UN-SiC system in the present invention is that only a small amount of SiC added phase (<10 vol%) is required to significantly improve the antioxidant performance of UN.

[0025] 3. The SiC-modified UN-based composite fuel pellets proposed in the present invention are scientifically designed and simple in method. Their antioxidant properties are significantly improved compared to pure UN fuel pellets. By regulating the morphology and distribution of the SiC second phase in the UN-based composite fuel pellets, uniform dispersed distribution or three-dimensional continuous distribution of SiC particles or whiskers in the UN matrix is ​​achieved, further improving the antioxidant properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The microstructure diagram of the UN-based composite fuel pellets with uniformly dispersed SiC particles (a), the microstructure diagram of the UN-based composite fuel pellets with uniformly dispersed SiC whiskers (b), and the microstructure diagram of the UN-based composite fuel pellets with three-dimensional continuous SiC distribution (c) in the present invention;

[0027] Figure 2 This is a comparison chart of the dynamic oxidation curves of the SiC modified UN composite pellet in Example 1 of the present invention and the pure UN pellet in Comparative Example 1. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0030] The antioxidant UN-based composite fuel pellet described in the present invention uses silicon carbide (SiC) as the antioxidant performance enhancing phase of the UN fuel pellet, so that SiC is dispersedly distributed or three-dimensionally continuously distributed in the UN fuel matrix, and utilizes the intracrystalline-grain boundary synergistic strengthening effect of SiC to achieve a significant improvement in the antioxidant performance of the UN fuel pellet.

[0031] Specifically, the intragranular modification produced by the solid solution reaction of trace SiC and UN can effectively enhance the intrinsic antioxidant properties of the UN matrix, while the excellent chemical inertness of the SiC second phase itself can effectively inhibit grain boundary oxidation. By optimizing the morphology and distribution of the SiC second phase in the composite fuel pellets, the antioxidant properties of the composite fuel pellets can be further improved.

[0032] Specifically, the volume fraction of UN in the raw material of the required UN-based composite fuel is 90 vol%-99.5 vol%, and the volume fraction of SiC is 0.5 vol%-10 vol%.

[0033] Specifically, the SiC can be replaced by one or more mixtures of titanium carbide (TiC), zirconium carbide (ZrC), hafnium carbide (HfC), niobium carbide (NbC), tantalum carbide (TaC), vanadium carbide (VC), molybdenum carbide (MoC), etc. that can undergo modification reactions with UN; the SiC can also be replaced by a mixture of SiC and at least one of TiC, ZrC, HfC, NbC, TaC, VC, and MoC.

[0034] The present invention provides a method for preparing an oxidation-resistant uranium nitride composite fuel pellet with SiC dispersed distribution, comprising the following steps:

[0035] Step 1: Mix uranium nitride powder and nano silicon carbide powder to obtain mixed raw material powder.

[0036] Specifically, the nano silicon carbide powder is any one of SiC particles and SiC whiskers or a mixture of the two; the particle size of the SiC particles is 0.06-50 μm, the diameter of the SiC whiskers is 0.1-2 μm, and the length is 10-300 μm; the particle size of the UN powder is 0.3-50 μm, 235 The enrichment of U is 0.3%-19%.

[0037] Step 2: Sintering and cooling the mixed raw material powder obtained in step 1 to obtain oxidation-resistant uranium nitride composite fuel pellets with SiC dispersed therein.

[0038] The present invention also provides a method for preparing an oxidation-resistant uranium nitride composite fuel pellet having SiC in a three-dimensional continuous distribution, comprising the following steps:

[0039] Step 1: Prepare UN low-density blank from UN powder.

[0040] Specifically, in step 1, the particle size of the UN powder is 0.3-50 μm. 235 The enrichment of U is 0.3%-19%; the density of UN low-density blank is 7-12g / cm 3 The specific method for preparing UN low-density blanks includes low-temperature pre-sintering or room-temperature dry pressing, and the low-temperature pre-sintering method is any one of pressureless sintering, gas pressure sintering, hot pressing sintering, hot isostatic pressing sintering, and spark plasma sintering.

[0041] Step 2: crushing, screening, grinding and spheroidizing the UN low-density blank to obtain spherical UN;

[0042] Step 3: Mix the spherical UN with nano-SiC particles, so that the nano-SiC particles are evenly coated on the surface of the spherical UN to obtain SiC-UN composite powder with a core-shell structure;

[0043] Step 4: Sintering and cooling the SiC-UN composite powder to obtain an oxidation-resistant uranium nitride composite fuel pellet with three-dimensional continuous SiC distribution.

[0044] Example 1

[0045] A method for preparing an oxidation-resistant uranium nitride composite fuel pellet with dispersed nano-SiC particles comprises the following steps:

[0046] Step 1: The average particle size is 3 μm. 235 Uranium nitride powder with a U enrichment of 5% and nano silicon carbide powder with an average particle size of 0.1 μm are mixed to obtain a mixed raw material powder.

[0047] Specifically, the volume fraction of the nano-SiC particles in the mixed raw material powder is 10%, and the volume fraction of UN is 90%.

[0048] Step 2: The mixed raw material powder obtained in step 1 is placed in a graphite mold for spark plasma sintering, and after cooling, an oxidation-resistant uranium nitride composite fuel pellet with dispersed nano-SiC particles is obtained, such as Figure 1 (a) shown.

[0049] Specifically, the sintering process is as follows: heating rate is 200℃ / min, sintering temperature is 1500℃, holding time is 10min, mechanical pressure is 70MPa, and sintering atmosphere is vacuum; in addition, the dynamic oxidation temperature of the oxidation-resistant uranium nitride composite fuel pellets with dispersed nano-SiC particles is more than 50℃ higher than that of pure UN.

[0050] Example 2

[0051] A method for preparing an oxidation-resistant uranium nitride composite fuel pellet with dispersed SiC whiskers comprises the following steps:

[0052] Step 1: The average particle size is 1 μm. 235 Uranium nitride powder with a U enrichment of 5% is mixed with SiC whiskers with an average diameter of 1 μm and a length of 10 μm to obtain a mixed raw material powder.

[0053] Specifically, the volume fraction of SiC whiskers in the mixed raw material powder is 6%, and the volume fraction of UN is 94%.

[0054] Step 2: The mixed raw material powder obtained in step 1 is placed in a graphite mold for sintering and cooling to obtain an oxidation-resistant uranium nitride composite fuel pellet with dispersed SiC whiskers, such as Figure 1 (b) as shown.

[0055] Specifically, the sintering process is as follows: heating rate is 20°C / min, sintering temperature is 1550°C, holding time is 60min, mechanical pressure is 50MPa, and sintering atmosphere is vacuum; in addition, the dynamic oxidation temperature of the oxidation-resistant uranium nitride composite fuel pellets with dispersed SiC whiskers is more than 50°C higher than that of pure UN.

[0056] Example 3

[0057] A method for preparing an oxidation-resistant uranium nitride composite fuel pellet with three-dimensionally continuously distributed nano-SiC comprises the following steps:

[0058] Step 1: The average particle size is 5 μm. 235 UN powder with U enrichment of 5% is pre-sintered at low temperature in a pressureless sintering furnace to prepare UN low-density blank.

[0059] Specifically, the density of the UN low-density blank is 9g / cm 3 .

[0060] Step 2: Crush, screen, grind and spheroidize the UN low-density blank to obtain spherical UN.

[0061] Specifically, the crushing is carried out by mechanical crushing, and the UN particles with a size of 15-100 mesh are obtained by sieving.

[0062] Step 3: Mix the spherical UN with nano-SiC particles so that the nano-SiC particles are evenly coated on the surface of the spherical UN to obtain SiC-UN composite powder with a core-shell structure.

[0063] Specifically, spherical UN and nano-SiC particles with an average particle size of 0.1 μm are placed in a coating device and mixed, and the volume fraction of SiC in the composite powder is 5%, and the volume fraction of UN is 95%.

[0064] Step 4: The SiC-UN composite powder is subjected to spark plasma sintering and cooling to obtain an oxidation-resistant uranium nitride composite fuel pellet with SiC in a three-dimensional continuous distribution, such as Figure 1 (c) as shown.

[0065] Specifically, the sintering process is as follows: the heating rate is 100°C / min, the sintering temperature is 1650°C, the holding time is 5min, the mechanical pressure is 50MPa, and the sintering atmosphere is vacuum; in addition, the obtained SiC is three-dimensionally continuously distributed and the oxidation-resistant uranium nitride composite fuel pellet has significantly enhanced oxidation resistance compared with pure UN, and the dynamic oxidation temperature is more than 60°C higher than that of pure UN.

[0066] Comparative Example 1

[0067] A method for preparing pure UN nuclear fuel pellets comprises the following steps:

[0068] (1) The average particle size is 2 μm, 235 UN powder with U enrichment of 1% was pressed under a pressure of 300 MPa to form a green blank to be sintered.

[0069] (2) Place the green blank to be sintered into a spark plasma sintering furnace, set the sintering process parameters, including a heating rate of 10°C / min, a sintering temperature of 1700°C, a holding time of 5 min, and a sintering atmosphere of nitrogen. Start the sintering program and sinter. After sintering, cool it with the furnace.

[0070] (3) After cooling, take out the UN pellet.

[0071] The dynamic oxidation curve comparison of pure UN pellets in Comparative Example 1 is as follows: Figure 2 shown.

[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0073] The above specific implementation methods are detailed descriptions of the present invention. It cannot be determined that the specific implementation methods of the present invention are limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions and substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. An oxidation-resistant uranium nitride-based composite fuel pellet, characterized in that: The invention comprises a uranium nitride matrix and silicon carbide, wherein the volume fraction of the uranium nitride is 90 vol%-99.5 vol%, and the volume fraction of the silicon carbide is 0.5 vol%-10 vol%.

2. The oxidation-resistant uranium nitride-based composite fuel pellet according to claim 1, characterized in that: The silicon carbide is dispersedly distributed or three-dimensionally continuously distributed in the uranium nitride matrix.

3. A method for preparing an oxidation-resistant uranium nitride composite fuel pellet with SiC dispersed distribution, characterized in that: The steps include: Step 1: Mixing uranium nitride powder and nano silicon carbide powder to obtain mixed raw material powder; Step 2: Sintering and cooling the mixed raw material powder obtained in step 1 to obtain oxidation-resistant uranium nitride composite fuel pellets with SiC dispersed therein.

4. The method for preparing a SiC dispersedly distributed oxidation-resistant uranium nitride composite fuel pellet according to claim 3, characterized in that: In step 1, the nano silicon carbide powder is SiC particles and / or SiC.

5. The method for preparing an oxidation-resistant uranium nitride composite fuel pellet with SiC dispersed distribution according to claim 4, characterized in that: The SiC particles have a particle size of 0.06-50 μm, and the SiC whiskers have a diameter of 0.1-2 μm and a length of 10-300 μm.

6. The method for preparing an oxidation-resistant uranium nitride composite fuel pellet with SiC dispersed distribution according to claim 3, characterized in that: In step 1, the particle size of the uranium nitride powder is 0.3-50 μm. 235 The enrichment of U is 0.3%-19%.

7. A method for preparing an oxidation-resistant uranium nitride composite fuel pellet with three-dimensional continuous distribution of SiC, characterized in that: The steps include: Step 1: Prepare UN low-density blank from UN powder; Step 2: crushing, screening, grinding and spheroidizing the UN low-density blank to obtain spherical UN; Step 3: Mix the spherical UN with nano-SiC particles, so that the nano-SiC particles are evenly coated on the surface of the spherical UN to obtain SiC-UN composite powder with a core-shell structure; Step 4: Sintering and cooling the SiC-UN composite powder to obtain an oxidation-resistant uranium nitride composite fuel pellet with three-dimensional continuous SiC distribution.

8. The method for preparing an oxidation-resistant uranium nitride composite fuel pellet with three-dimensionally continuously distributed SiC according to claim 7, characterized in that: In step 1, the particle size of UN powder is 0.3-50μm. 235 The enrichment of U is 0.3%-19%.

9. The method for preparing an oxidation-resistant uranium nitride composite fuel pellet with three-dimensionally continuous SiC distribution according to claim 7, characterized in that: In step 1, the density of UN low-density blank is 7-12g / cm 3 .

10. The method for preparing an oxidation-resistant uranium nitride composite fuel pellet with three-dimensionally continuously distributed SiC according to claim 7, characterized in that: In step 1, the specific method for preparing the UN low-density blank includes low-temperature pre-sintering or room-temperature dry pressing.

11. The method for preparing an oxidation-resistant uranium nitride composite fuel pellet with three-dimensionally continuously distributed SiC according to claim 10, characterized in that: The low temperature pre-sintering method is any one of pressureless sintering, gas pressure sintering, hot pressing sintering, hot isostatic pressing sintering, and spark plasma sintering.

Citation Information

Cited By

  • Nuclear fuel and preparation method thereof

    CN120977620A